Never Again: Reflections on Environmental Responsibility after Roe 8 - Gaynor, A.; Newman, Peter; Jennings, P. (UWA Publishing, 2017)
The lead-up to the 2017 Western Australian state election saw a large and lively protest over the construction of stage 8 of the Roe Highway (Roe 8) and the Perth Freight Link. Years of opposition to Roe 8 culminated in civil disobedience, mass arrests and media theatrics as the bulldozers tore across Aboriginal heritage sites and through much-loved bushland and wetland just weeks out from an election the government appeared likely to lose. When Labor was swept to power in the biggest landslide victory ever delivered by Western Australian voters the Roe 8 contracts were cancelled. However, the planning systems that enabled Roe 8 and the Perth Freight Link remain in place, and in need of reform. This book illuminates what was at stake in the conflict, for Perth residents, Aboriginal heritage and the environment. It traces the history of Roe 8 and the Perth Freight Link to show what needs to be done in order to ensure that Western Australian people and environments never again have such a damaging project thrust upon them. It surveys the issues and makes recommendations across transport, planning, environment, health and Aboriginal heritage policy areas. It also captures the nature of the diverse and vigorous resistance to the project, setting the struggle and its bittersweet victory in a wider context.